Shimazaki Tôson : the maker of modern Japanese literature : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Japanese at Massey University - Arai, Masahiko (Massey University, 1997)
This thesis traces the development of Shimazaki Tôson (1872-1943) from his earliest work through to the final summit of his literary career, the novel Yoake mae (Before the Dawn). It examines the way in which the writer responded to the influx of Western culture and ideas that characterised early- to mid-Meiji Japan, and the way in which, in the course of integrating these influences, he evolved a view of nature and of man's place in it, and an approach to the craft of letters, that enabled him to produce compelling works of fiction and to earn his reputation as the father of modern Japanese literature. In particular, the thesis identifies a variety of specific factors that successively influenced Tôson's development. The works of Rousseau and of the English Romantic poets, and the view of nature and of the individual's place within it found in Protestant Christianity, are identified as decisive influences on the poetry of his early manhood, a significant part also being played by his mentor of that time and leader of the Bungakkai group, Kitamura Tôkoku (1868-1894). Subsequent key influences are identified as: the emphasis on objective observation and enquiry found in both Western science (epitomised by Darwinism) and aesthetic theory (in particular the work of Ruskin), the painting of the French Impressionist Millet, and the writings of Turgenev and Dostoevsky. The thesis shows how, in absorbing and integrating these influences, Tôson consciously practised to develop his observational and descriptive technique, and demonstrates the results of this self-training in the works Tôson produced after turning from poetry to prose, particularly the powerful visual impact of his descriptive writing. The thesis shows how subsequently Tôson combined the confessional impulse gained from Rousseau and the disciplined objectivity of the scientific spirit, to create powerful works of naturalistic autobiographical fiction. It demonstrates in particular Tôson's use of nature-description to achieve functional narrative goals, and not merely as decoration. In considering his final masterpiece (written and serialised during the period 1929-1935), the thesis examines how Tôson applied the creative methods he had developed thus far to the writing of fiction set in the context of decisive events in Japan's modem history.
Keywords: Shimazaki, Tôson 1872-1943; Criticism and interpretation